Gamified English Vocabulary Puzzle Game with FSM-Based Emotional Feedback and Fisher–Yates Shuffle - Muhammad Fachrul Reihan Fauzian; Rio Andriyat Krisdiawan; Nida Amalia Asikin (Media Jurnal Informatika, 2026)
English vocabulary learning among elementary school students often faces challenges related to low engagement, repetitive practice activities, and limited interactive feedback in conventional learning media. Educational games with gamification elements can provide a more engaging learning environment, while rule-based character feedback and randomized puzzle arrangements may improve gameplay variation and user interaction. Objective: This study aimed to develop an Android-based English vocabulary puzzle game that integrates gamification elements, an FSM-based emotional feedback mechanism, and the Fisher–Yates Shuffle algorithm for sixth-grade elementary school students. Methods: The game was developed using the Game Development Life Cycle (GDLC) method through initiation, pre-production, production, testing, beta, and release stages. The application was implemented using Unity and C#, with Firebase Realtime Database used for data management. System evaluation was conducted through Black Box Testing, White Box Testing, and User Acceptance Testing involving 35 sixth-grade students of SD Negeri 2 Cikeusal. Results: The developed game successfully implemented gamification elements, including scores, levels, time limits, life indicators, and visual character feedback. The FSM-based mechanism generated predefined emotional responses through thirteen states and seventeen events, while the Fisher–Yates Shuffle algorithm produced varied puzzle arrangements. Black Box Testing confirmed that all main features functioned as expected, and White Box Testing verified the control flow of the FSM and Fisher–Yates Shuffle implementations. User Acceptance Testing produced an overall acceptance score of 94.3%, indicating that the game was well accepted by users. Conclusion: The integration of gamification, FSM-based emotional feedback, and Fisher–Yates Shuffle  indicates its potential to provide an engaging and interactive medium for English vocabulary practice. However, this study evaluated user acceptance and system functionality, not direct vocabulary learning improvement.